Industrial process plant construction estimating and man-hour analysis - Storm, Kenneth (Gulf Professional Publishing, 2019)
Industrial Process Plant Construction Estimating and Man-Hour Analysis focuses on industrial process plants and enables the estimator to apply statistical applications, estimate data tables, and estimate sheets to use methods for collecting, organizing, summarizing, presenting and analyzing historical man-hour data. The book begins with an introduction devoted to labor, productivity measurement, collection of historical data, verification of data, estimating methods, and factors affecting construction labor productivity and impacts of data. It goes on to explore construction statistics and mathematical spreadsheets that are followed by detailed scopes of work, ranging from coal-fired power plants, to oil refineries and solar plants, among others. This book will aid industrial project managers, estimators and engineers with the level of detail and practical utility for today's industrial operations. It is an ideal resource for those involved in engineering, technology and construction estimation. Teachers users how to use day-to day worksheets to estimate equipment and piping for all process plants and power plant projectsIdentifies quantity differences with the comparison method and eliminates impacts between proposed and previously installed equipment applicable for any complexity of design, bid and contractHelps users understand how to implement statistical and estimating methods, scopes of work, man-hour tables and estimate sheets to produce direct craft man-hour estimates, RFPs and field change orders